Differential nutritional, endocrine, and cardiovascular effects in obesity-prone and obesity-resistant rats fed standard and hypercaloric diets - Oliveira Junior, Silvio A. [UNESP]; Pai-Silva, Maeli Dal; Martinez, Paula F. [UNESP]; Campos, Dijon H. S. [UNESP]; Lima-Leopoldo, Ana P. [UNESP]; Leopoldo, André S. [UNESP]; Nascimento, André F. [UNESP]; Okoshi, Marina P. [UNESP]; Okoshi, Katashi [UNESP]; Padovani, Carlos R. [UNESP]; Cicogna, Antonio C. [UNESP] (My University, 2010)
Background: This study tested whether rats with obesity induced by a hypercaloric diet (HD) present higher nutritional, endocrine, and cardiovascular disturbances compared with counterparts with obesity induced by overfeeding of a standard diet. An additional objective was to compare the isolated influence of HD on these parameters in lean and obese rats. Material/Methods: Twenty Wistar-Kyoto rats were distributed into four groups: CD-lean, CD-obese, HD-lean, and HDobese. CD (control diet) and HD groups received commercial standard chow and HD, respectively, for 20 weeks. The lean and obese groups included obesity-resistant and obesity-prone animals, respectively. Nutritional and metabolic evaluation involved measurement of calorie intake, dietary efficiency, body weight, adiposity, glycemia, triacylglycerol, insulin, and leptin. Cardiovascular evaluation included systolic blood pressure measurement, echocardiography, and analyses of myocardial morphology and myosin heavy-chain composition. Results: In both diets, obesity was characterized by increased adiposity, hyperleptinemia, hypertriacylglycerolemia, hyperinsulinemia, and cardiomyocyte nuclear hypertrophy. HD promoted hyperleptinemia and cardiac remodeling, characterized by nuclear and ventricular hypertrophy, as well as improved systolic performance in both the obesity-prone and obesity-resistant biotypes. In contrast to HD-lean, HD-obese rats presented more accentuated endocrine responses, including hyperglycemia, lower glycemic tolerance, and hyperleptinemia as well as interstitial fibrosis compared with the CD-obese animals. Conclusions: This study confirmed the primary hypothesis that rats with HD-induced obesity present more accentuated nutritional and endocrine disturbances compared with their counterparts with obesity resulting from overfeeding. In addition, dietary effects were more important between the obese groups, supporting evidence of an interaction between diet and biotype. © Med Sci Monit, 2010.
Keywords: Cardiac remodeling; Endocrine; Hypercaloric diet; Obesity; Rats